The Implementation of Learning Aqidah Akhlak on Students Behavior at Madrasah Ibtidayah - Anissatul Faqziaty; Anwar Mahmudi; Fiyya Zahrotul Firdausi; Muhammad Iqbaludin; Mohamad Ishak; Muhammad Yahya; Pita Andri Yani; Rika Sulastri; Salbiyah Salbiyah (Bulletin of Pedagogical Research, 2021)
Moral and religious (aqidah) education plays a significant role in shaping children's behavior. Morality, as reflected in ethical conduct, and aqidah, as a belief system, are interconnected elements that influence personal development. This study aims to examine the impact of moral education and the application of aqidah on fostering positive behavior in children. Children who receive moral and religious instruction tend to develop a more positive worldview, form healthy relationships with others, and grow into individuals who are kind, patient, and tolerant. This education provides them with a solid moral foundation, equipping them to face challenges and resist negative influences in their environment. The integration of moral and aqidah education into religious or character education curricula within formal educational settings is essential. Furthermore, a comprehensive approach involving families, communities, and educational institutions can effectively reinforce these teachings and shape children’s behavior. In conclusion, moral and aqidah education significantly influences children’s behavior, helping them grow into morally upright individuals who can contribute positively to society.